2016
DOI: 10.5455/ijmsph.2016.13032015126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and response in patients with megaloblastic anemia

Abstract: Background: Megaloblastic anemia is one of the frequently occurring diseases in a developing country such as India. Megaloblastic anemia occurs mainly because of vitamin B12 and folate deficiency, but in some cases, it may occur owing to the causes affecting the metabolism of vitamins or the defect in DNA synthesis. Very few studies have been conducted to study the prevalence of megaloblastic anemia in the general population. Objective: To find out the age-wise pattern with its clinical profile and response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
4
3
0
1
Order By: Relevance
“…Pandya H et al found the Incidence of megaloblastic anemia highest in the age between 40 and 49 years. 16 In the present study, male preponderance was observed in megaloblastic anemia. Similar finding was observed by Daljinder Kaur et al, Pandya et al 17,16 Other studies observed female preponderance in megaloblastic anemia.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Pandya H et al found the Incidence of megaloblastic anemia highest in the age between 40 and 49 years. 16 In the present study, male preponderance was observed in megaloblastic anemia. Similar finding was observed by Daljinder Kaur et al, Pandya et al 17,16 Other studies observed female preponderance in megaloblastic anemia.…”
Section: Discussionsupporting
confidence: 54%
“…16 In the present study, male preponderance was observed in megaloblastic anemia. Similar finding was observed by Daljinder Kaur et al, Pandya et al 17,16 Other studies observed female preponderance in megaloblastic anemia. 18,19 In the present study, the mean serum LDH level was found to be highest in megaloblastic anemia with LDH activity showing 19 times increase as compared to control.…”
Section: Discussionsupporting
confidence: 54%
“…These results were in contrast with findings of a study by Pandya et al, which showed that males were more affected from megaloblastic anemia than the females and showed peak incidence in age groups of 40-49 years which is a much older age group than our study findings. 13 A similar study to our study results were a study by Amrapal et al, which found a peak age incidence in megaloblastic patients between age groups of 11-40 years 2. The difference of gender between our study and these studies might be due to cultural differences.…”
Section: Discussionsupporting
confidence: 92%
“…Icterus similar to previous studies like the one by Pandya and Patel 14 where maximum patients were in the age group 40-49 years and an overall male preponderance was seen.…”
Section: Discussionsupporting
confidence: 90%